2015
DOI: 10.1039/c5sm02143j
|View full text |Cite
|
Sign up to set email alerts
|

New insight into icing and de-icing properties of hydrophobic and hydrophilic structured surfaces based on core–shell particles

Abstract: Icing is an important problem, which often leads to emergency situations in northern countries. The reduction of icing requires a detailed understanding of this process. In this work, we report on a systematic investigation of the effects of geometry and chemical properties of surfaces on the formation of an ice layer, its properties, and thawing. We compare in detail icing and ice thawing on flat and rough hydrophilic and hydrophobic surfaces. We also show advantages and disadvantages of the surfaces of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…82 This ''structuring'' effect has also been put forward as a key factor regarding the ice nucleating ability of a given surface. 83,84 Here, we focus on the orientational order of the water molecules, as a function of their distance from the centre of the bilayers. In particular, we have investigated the changes in the average value of the angle y defined by the water dipole moment and the z-axis of the simulation box (perpendicular to the bilayers plane).…”
Section: Water Orientationmentioning
confidence: 99%
“…82 This ''structuring'' effect has also been put forward as a key factor regarding the ice nucleating ability of a given surface. 83,84 Here, we focus on the orientational order of the water molecules, as a function of their distance from the centre of the bilayers. In particular, we have investigated the changes in the average value of the angle y defined by the water dipole moment and the z-axis of the simulation box (perpendicular to the bilayers plane).…”
Section: Water Orientationmentioning
confidence: 99%
“…The literature on the adhesion between frozen oil and micropatterned surfaces is limited; but many efforts have been devoted to exploring possible strategies to remove ice from surfaces, which can all be categorized into either passive strategies or active strategies [184,185,218]. The passive strategy is implemented either by controlling the surface wettability to reduce ice adhesion or by applying mechanical forces to remove the accumulated ice [184,185,218]. This is because superhydrophobic surfaces can be used to delay the ice formation and reduce the contact area, thereby reducing the shear forces between the ice and substrates.…”
Section: Bio-inspired Superhydrophobic Superhydrophilic and Supementioning
confidence: 99%
“…Among these methods, thermal melting uses sources such as warm air or electrical current and is regarded as one of the most effective ways to remove ice [183,219,220]. One decade-old traditional approach is warm air melting, in which intense warm air is blown onto objects through a special tube [184,185,218]. This raises the temperature of the system quickly, resulting in the melting of ice [183].…”
Section: Bio-inspired Superhydrophobic Superhydrophilic and Supementioning
confidence: 99%
“…24−26 Therefore, the antifreeze liquids were introduced as one component of the slippery liquid lubricants to reduce the freezing point as well as decrease the application cost simultaneously. 27,28 It is well known that the successful construction of a hierarchical micro-/nanosacle rough structure is remarkably crucial for the achievement of SLIPS. 29,30 In our previous work, we have confirmed that the magnetic Fe 3 O 4 nanoparticles are favorable for forming the micro-/nanoscale hierarchical structures.…”
Section: Introductionmentioning
confidence: 99%